Continuous Professional Oral Health Care Intervention Improves Severe Aspiration Pneumonia - Wakako Nawata; Yojiro Umezaki; Masahiro Yamaguchi; Masato Nakajima; Michiko Makino; Masahiro Yoneda; Takao Hirofuji; Takafumi Yamano; Hiroaki Ooboshi; Hiromitsu Morita (Case Reports in Dentistry)
Professional oral health care (POHC) is known to prevent aspiration pneumonia in patients with dysphagia and/or those at the perioperative stage of surgery. However, the effect of POHC on patients suffering from aspiration pneumonia remains unknown. Here, we report a case where continual POHC intervention improved severe aspiration pneumonia. A 74-year-old male patient with a brain infarction suffered from severe aspiration pneumonia (PSI: IV, A-DROP: 3) complicated by vascular dementia and severe dysphagia. Because an antimicrobial approach following the treatment guidelines for pneumonia was not effective, we started a POHC intervention to improve his poor oral condition at the request of the attending doctor and the patient’s family. The severe pneumonia markedly improved after continual POHC by the dental team. This case suggests that continual POHC intervention by a dental hygienist may improve severe aspiration pneumonia.